User Placement of a Visual Aid for Detecting Critical Signals in Fetal-Heart Rate Tracings: A Yoke-Control Study. (September 2014) - Ashdown, Amanda J.; Scerbo, Mark W.; Anderson-Montoya, Brittany L.; Belfore, Lee A.; Abuhamad, Alfred Z.; Davis, Stephen S.
The present study examined the ability of participants to detect critical signals embedded within dynamic fetal-heart rate (FHR) tracings using a visual aid. Participants inspected tracings for deviations in the FHR under different levels of heart rate variability. One group was given control over placement of the visual aid. A second yoke-control group monitored the same presentation of critical signals and aid placements but could not alter the visual aids. In phase 1, student participants placed the aid and in phase 2 the experimenter placed the aid. Performance was compared to a control group that had no aids. The results showed that no group detected all critical signals but those who placed the aid performed better than those who had no aid across all levels of heart rate variability. However, the benefit of the visual aid for the yoke-control participants was limited to the condition where the experimenter placed the aid. These results suggest that a visual aid can improve performance, but that it does not completely overcome the challenge detecting critical signals in FHR tracings.